The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1002/jcp.29129
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA HOTAIR upregulates autophagy to promote apoptosis and senescence of nucleus pulposus cells

Abstract: Intervertebral disc degeneration (IDD) is a complex and chronic disease that involves disc cell senescence, death, and extracellular matrix (ECM) degradation. HOTAIR, a long non-coding RNA (lncRNA) is reportedly associated with autophagy, whereas autophagy is shown to promote IDD. However, how it affects nucleus pulposus (NP) cells, the primary component of intervertebral discs is still unclear. We hypothesized that HOTAIR promotes NP cell apoptosis and senescence through upregulating autophagy. Thus, silencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 59 publications
0
47
1
Order By: Relevance
“…Accumulating evidence suggests that lncRNAs play a critical role in IVDD progression through modulating various cellular processes, such as autophagy, senescence, proliferation, and ECM synthesis (33,34). A previous study demonstrated that lncRNA FAM83H-AS1 contributes to NP cell growth through the regulation of the Notch signaling pathway (31).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggests that lncRNAs play a critical role in IVDD progression through modulating various cellular processes, such as autophagy, senescence, proliferation, and ECM synthesis (33,34). A previous study demonstrated that lncRNA FAM83H-AS1 contributes to NP cell growth through the regulation of the Notch signaling pathway (31).…”
Section: Discussionmentioning
confidence: 99%
“…The role of long-chain non-coding RNA (lnc RNA) has attracted widespread attention [33]. LncRNAs have been reported in nervous system disorders, metabolic diseases, reproductive development and cardiovascular diseases [34]. Recent study has con rmed that lncRNA may play an important role in cardiac regeneration and repair as a potential target of treatment [35].…”
Section: Discussionmentioning
confidence: 99%
“…Low levels of ERS often lead to autophagy; however, under high levels of ERS, autophagy is transiently activated and then accompanied by the activation of apoptosis, along with rapid inhibition of autophagy (Holczer et al, 2015). Additionally, autophagy or proteins involved in the process of autophagy may drive the activation of apoptosis and necrosis by breaking down indispensable components of the cells, which in turn facilitates cell death (Zhan et al, 2020). 3-methyladenine (3-MA), the PI3K inhibitor, was the first identified, and is the most widely used, autophagy inhibitor.…”
Section: Discussionmentioning
confidence: 99%